A High Efficient, Compact 4th Order CLCL Converter Features to Use Constant-Current Power Supply - Kamran Davoodi; Javad Shokrollah Moghani; sina salehi dobakhshari (AUT Journal of Electrical Engineering, 2019)
This paper presents a 4th order CLCL resonant converter which is suitable for constant current power supply applications. This converter is designed with Immittance characteristic with two inductors and two capacitors in resonant network. A detailed analysis and design process of a 200w converter as a constant current supply have been provided and simulation results are verified with results of a constructed converter. In analyzing this converter, the AC analysis method is used. This converter with its unique structure, a combination of series and parallel resonant converter, has the advantages of both. As a constant current supply, CLCL resonant converter has the advantages of rigidity against short circuit even without a controller, easy operation in parallel mode, low circulating currents and high efficiency due to its soft switching operation. For this converter, leakage and magnetizing inductance of a transformer can be used as a part of the resonance network and it decreases the converter size. Also series capacitor, eliminates the DC component and prevents the transformer saturation in unbalance conditions. With fixed-frequency performance, filter design also will be easier. Considering these advantages, the proposed topology can be used in a variety of applications such as magnetic power supplies, capacitor charging power supplies and agitator for laser diodes.